POLITIK HUKUM PENGATURAN TELEMEDICINE DI INDONESIA BERDASARKAN PERATURAN MENTERI KESEHATAN NOMOR 20 TAHUN 2019 TENTANG PENYELENGGARAAN PELAYANAN TELEMEDICINE ANTAR FASILITAS PELAYANAN KESEHATAN - Bangun Risael Ikhsan; Mexsasai Indra; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
Health is a human right and one of the elements of welfare that must berealized. The times and technology have made progress in the field of health andmedical science, such as online doctors who use web-based health services andapplications, known as telemedicine. The existence of telemedicine certainly has animpact and influence on the birth of a regulation or rule which regardingtelemedicine is regulated through the Minister of Health Regulation Number 20 of2019. The regulation of telemedicine which is regulated in the Minister of HealthRegulation Number 20 of 2019 concerning Telemedicine, regulates the presence ofdoctors and health service facilities that use the website and an application toconnect patients with doctors which is done online. the presence of a rule of courseto provide legal certainty, justice and benefit where the Minister of HealthRegulation Number 20 of 2019 concerning Telemedicine is the legal umbrella fortelemedicine.The results of this study examine and analyze the current regulations,namely the Minister of Health Regulation Number 20 of 2019 as a legal umbrellaregarding telemedicine where the regulation and content of this Minister of Healthdoes not provide legal certainty and regulations regarding telemedicine have beenleft behind from the development of progress in the health sector which is notfollowed by developments. constitutional law in legal reform in the health sector,especially in terms of regulations regarding telemedicine, the ideal concept of theaspired law (ius constituendum) regarding the regulation of telemedicine must referto the Health Act and the Law on Medical Practice as well as the Minister ofHealth's Regulation on telemedicine as well must contain content about thefulfillment of health in remote areas and regional responsibilities in the fulfillmentand implementation of telemedicine so that the issuance of regulations that trulyprovide certainty to the community as a form of fulfillment of the concept ideal ofa rule.Keywords: telemedicine, implementation of telemedicine, legal politics.